Tiktok as a new paradigm for information in the Ukrainian War. A study from the West of the initial coverage of the conflict through this platform - Sidorenko, Pavel; Alonso López, Nadia; Paíno Ambrosio , Adriana (Estudios sobre el Mensaje Periodístico, 2023)
Since social networks emerged as sources of information from the first moment when Russia decided to invade Ukraine in February 2022, this research aims to analyze, in an exploratory way, the type of profiles that initially spread the Ukrainian war through TikTok, a trending social network based on entertainment with a narrative characterized by satire, challenges, and viral dances. For this purpose, a qualitative analysis of the publications made on this social network with the hashtags #Ukraine and #Ukraine is used taking into account that both civilians and journalists or military made use of the platform. The results show that influencers’ profiles are the ones that publish more information and testimonial content and have a greater impact than the media themselves.